Relevant Aspects of Recommendations for Clinic Prevention in Elderly - 2013 - Villas Boas, Paulo J.F.; Vidal, Edson I. de O.; Mondelli, Alessandro L.; Valle, Adriana P. do; Wachholz, Patrick A.; Oliveira, Gabriel M. de (Medicina (Ribeirao Preto), 2013)
The American Academy of Family Physicians (AAFP) updated, in 2012, the “Recommendations for Clinical Preventive Services.”, based on the homonymous publication by the United States Preventive Services Task Force (USPSTF). These recommendations are provided as an aid for physicians in clinical decision making regarding the care of their patients. They reflect the best clinical evidence available at the time of publication. It should be used with the clear understanding that development of new knowledge may consequently result in updates and modifications at the recommended statements. Some recommendations of the USPSTF are important in clinical practice with the elderly, being presented in conjunction with other scientific societies.